Assessment of nociception and related quality-of-life measures in a porcine model of neurofibromatosis type 1. Issue 11 (November 2019) - Khanna, Rajesh; Moutal, Aubin; White, Katherine A.; Chefdeville, Aude; Negrao de Assis, Pedro; Cai, Song; Swier, Vicki J.; Bellampalli, Shreya S.; Giunta, Marissa D.; Darbro, Benjamin W.; Quelle, Dawn E.; Sieren, Jessica C.; et al.
Abstract : Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder resulting from germline mutations in the NF1 gene, which encodes neurofibromin. Patients experience a variety of symptoms, but pain in the context of NF1 remains largely underrecognized. Here, we characterize nociceptive signaling and pain behaviors in a miniswine harboring a disruptive NF1 mutation (exon 42 deletion). We present the first characterization of pain-related behaviors in a pig model of NF1, identifying unchanged agitation scores, lower tactile thresholds (allodynia), and decreased response latencies to thermal laser stimulation (hyperalgesia) in NF1 +/ex42del (females only) pigs. Male NF1 +/ex42del pigs with tumors showed reduced sleep quality and increased resting, 2 health-related quality-of-life symptoms found to be comorbid in people with NF1 pain. We explore these phenotypes in relationship to suppression of the increased activity of the N-type voltage-gated calcium (CaV2.2) channel by pharmacological antagonism of phosphorylation of a regulatory protein—the collapsin response mediator protein 2 (CRMP2), a known interactor of neurofibromin, and by targeting the interface between the α subunit of CaV2.2 and the accessory β-subunits with small molecules. Our data support the use of NF1 +/ex42del pigs as a large animal model for studying NF1-associated pain and for understanding the pathophysiology of NF1. Our findings demonstrate the translational potential of 2 small molecules in reversing ion channel remodeling seen in NF1. Interfering with CaV2.2, a clinically validated target for pain management, might also be a promising therapeutic strategy for NF1-related pain management. Abstract : Supplemental Digital Content is Available in the Text.A porcine model of neurofibromatosis type 1 (NF1) presents with allodynia, sexually dimorphic hyperalgesia, and poor quality of life.